Macrobenthic diversity, biomass and abundance in the Pechora Sea: a nine-year observational dataset from Vaigach Island (2015-2023) - Anna Gebruk; Polina Dgebuadze; Alexander B Basin; Miloslav Simakov; Alexey A Udalov; Margarita V Chikina; Olga Konovalova; Alexander Kokorin; Maria Mardashova; Nikolay Shabalin; Vadim Mokievsky (PANGAEA, 2025)
This dataset encompasses macrobenthic taxa collected across 9 annual field campaigns from 2015 to 2023 near Vaigach Island in the Pechora Sea, an ecologically significant area in the southeast of the Barents Sea. Macrobenthos were collected using Okean benthic grabs with a capture area of 0.1 m^2 or 0.175 m^2 aboard RV Kartesh. Bottom sediments retrieved by the benthic grabs were rinsed with pumped seawater through a 0.5-mm nylon mesh. Subsequently, the samples were preserved using a 4% formalin solution, followed by thorough rinsing and transfer into a 70% ethanol solution for long-term storage in the onshore laboratory. The coordinates of sampling stations, sample collection dates, and depths at the stations are provided within the dataset. For each sample, the wet biomass and abundance of each species are presented. All specimens of macrobenthos have been counted and weighed (wet biomass) with reported accuracy to 0.01 g. Bivalve molluscs and gastropods were weighed with shells. Taxonomic nomenclature was standardised using the World Register of Marine Species (WoRMS). A total of 243 samples yielded 353 taxa, with 214 identified to the species level, spanning 11 phyla and 28 classes of macrobenthic invertebrates.